INCIDENCIA DEL CRECIMIENTO ECONÓMICO EN LA DESIGUALDAD DE INGRESOS A NIVEL MUNDIAL Y POR NIVEL DE INGRESOS, UTILIZANDO TÉCNICAS DE COINTEGRACIÓN Y CAUSALIDAD CON DATOS DE PANEL, PERIODO 1980-2015 - Córdova Ramírez, Karina Mabel (2019)
This research examines the existence of an equilibrium and causality relationship between income inequality and economic growth worldwide and by income level in the period 1980-2015, using data from the World Bank panel (2016). To determine the long and short term equilibrium, were estimated the cointegration tests of Pedroni (1999) and Westerlund (2007), respectively. In addition, were estimated the force of the cointegration vector of Pedroni (2001) and the causality test of Dumitrescu. and Hurlin (2012) based on the causality test type Granger (1988). At a global level and in all groups of countries, there is a long-term and short-term equilibrium relationship between the study variables. In most countries the force of the cointegration vector is forceful with and without effect of time. At the global level, in the low-middle and low-income countries the force of the vector is forceful and significant with and without effect of time and in the countries of upper-middle income the force of the vector is forceful and significant without the effect of time. There is unidirectional causality, ranging from economic growth to income inequality, at the global level, in countries with medium-high and low incomes. Based on these results, the following policies aimed at reducing income inequality can be applied; first, increase in income tax; second, change of the productive matrix; third, investment in road infrastructure, education and basic services; fourth, generation of sources of employment, and; fifth, establishment or elevation of the